An in vitro assay for enzymatic studies on human ALG13/14 heterodimeric UDP-N-acetylglucosamine transferase - Wang, Chun-Di; Xu, Si; Chen, Shuai; Chen, Zheng-Hui; Dean, Neta; Wang, Ning; Gao, Xiao-Dong (Frontiers in Cell and Developmental Biology, 2022)
The second step of eukaryotic lipid-linked oligosaccharide (LLO) biosynthesis is catalyzed by the conserved ALG13/ALG14 heterodimeric UDP-N-acetylglucosamine transferase (GnTase). In humans, mutations in ALG13 or ALG14 14 lead to severe neurological disorders with a multisystem phenotype, known as ALG13/14-CDG (congenital disorders of glycosylation). How these mutations relate to disease is unknown because to date, a reliable GnTase assay for studying the ALG13/14 complex is lacking. Here we describe the development of a liquid chromatography/mass spectrometry-based quantitative GnTase assay using chemically synthesized GlcNAc-pyrophosphate-dolichol as the acceptor and purified human ALG13/14 dimeric enzyme. This assay enabled us to demonstrate that in contrast to the literature, only the shorter human ALG13 isoform 2, but not the longer isoform 1 forms a functional complex with ALG14 that participates in LLO synthesis. The longer ALG13 isoform 1 does not form a complex with Alg14 and therefore lacks GnTase activity. Importantly, we further established a quantitative assay for GnTase activities of ALG13- and ALG14-CDG variant alleles, demonstrating that GnTase deficiency is the cause of ALG13/14-CDG phenotypes.